2005
DOI: 10.1016/j.febslet.2005.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial peroxiredoxin 5 protects from mitochondrial DNA damages induced by hydrogen peroxide

Abstract: Peroxiredoxin 5 is a thioredoxin peroxidase ubiquitously expressed in mammalian tissues. Peroxiredoxin 5 can be addressed intracellularly to mitochondria, peroxisomes, the cytosol and the nucleus. Here, we show that mitochondrial human peroxiredoxin 5 protects mitochondrial DNA (mtDNA) from oxidative attacks. In an acellular assay, recombinant peroxiredoxin 5 was shown to protect plasmid DNA from damages induced by metal-catalyzed generation of reactive oxygen species. In Chinese hamster ovary cells, overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 41 publications
5
74
0
Order By: Relevance
“…Free radical balance is maintained by reduction of the superoxide anion to hydrogen peroxidase by superoxide dimutases. The resulting hydrogen peroxide can then be neutralized by various peroxidases, including peroxiredoxin-V (Banmeyer et al, 2005). Reduction in reactive oxygen species contributes to neuroprotection and can reduce the overall stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Free radical balance is maintained by reduction of the superoxide anion to hydrogen peroxidase by superoxide dimutases. The resulting hydrogen peroxide can then be neutralized by various peroxidases, including peroxiredoxin-V (Banmeyer et al, 2005). Reduction in reactive oxygen species contributes to neuroprotection and can reduce the overall stress response.…”
Section: Discussionmentioning
confidence: 99%
“…mtDNA is particularly susceptible to oxidative damage due to several factors; it is located close to the ROS-generating respiratory chain, it is not covered by histones, and it lacks a strong repair system compared with that of nuclear DNA. [52][53][54] Previous studies have revealed that there are decreased numbers of mitochondria in FECD endothelium, and that activity of cytochrome oxidase, the major respiratory chain enzyme, is decreased in the central area of FECD corneal buttons. 55 Based on our studies, these findings are consistent with oxidative stress-induced mtDNA damage that could lead to loss of integrity of inner mitochondrial membrane potential and apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…As antioxidant defense system, Peroxiredoxin (Prx) 3, Prx5, superoxide dismutase 2, and thioredoxin 2 eliminates ROS produced in mitochondria [30,31] . Knockout (KO) of Prx3 mice result in induction of oxidative damage [32] , KO of thioredoxin 2 mice showed an embryonic lethal phenotype [33] and KO of superoxide dismutase 2 mice die within 3 wk of birth because of mitochondrial into the matrix of mitochondria.…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%